Comparative Genomics and Phenotypic Investigations Into Antibiotic, Heavy Metal, and Disinfectant Susceptibilities of Salmonella enterica Strains Isolated in Australia - Wilson, Annaleise; Fox, Edward M.; Fegan, Narelle; Kurtböke, D. Ípek (Frontiers in Microbiology, 2019)
Salmonella enterica is recognized as a major contributor of gastrointestinal illness worldwide. Concerns have been raised over the increasing prevalence of antibiotic resistant strains of Salmonella isolated from animals and food, and the role of antibiotics and other antimicrobial agents such as biocides and heavy metals in the selection and dissemination of antibiotic resistant bacteria to human hosts. In this study the antibiotic, heavy metal and disinfectant resistance genotypes and phenotypes of 19 S. enterica isolates from food-producing animals were established using whole genome sequence analysis, and broth or agar dilution methods. This study also investigated the genomic environment of resistance genes on mobile genetic elements and chromosomal DNA. An ampicillin and streptomycin resistant S. Infantis isolate in this study harbored a β-lactamase (blaTEM-1), and two streptomycin resistance conferring genes (strA and strB) on a class 1 integron mobilized on a large conjugative plasmid. This plasmid also harbored two arsenic resistance gene cassettes. The arsenic resistance cassette, arsRCDAB, was also observed in two S. Singapore isolates with high tolerance to arsenate. A nalidixic acid resistant S. Typhimurium isolate was found to possess a mutation in gyrA resulting in amino acid change Asp87Gly and tetracycline resistant S. Typhimurium isolate was found to harbor efflux pump gene, tetA. No resistance (genotypic or phenotypic) was recorded to the disinfectants screened in this study. Taken together, results of this study showed a good correlation between predicted and measured resistances when comparing genotypic and phenotypic data, respectively. The findings of this study suggest that there are low levels of antibiotic resistance among Salmonella isolated from Australian food-producing animals.